2020
DOI: 10.1007/s10489-020-02051-1
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning system that generates quantitative CT reports for diagnosing pulmonary Tuberculosis

Abstract: The purpose of this study was to establish and validate a new deep learning system that generates quantitative computed tomography (CT) reports for the diagnosis of pulmonary tuberculosis (PTB) in clinic. 501 CT imaging datasets were collected from 223 patients with active PTB, while another 501 datasets, which served as negative samples, were collected from a healthy population. All the PTB datasets were labeled and classified manually by professional radiologists. Then, four state-of-the-art 3D convolution n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…According to previous studies, the use of deep learning models in pulmonary TB diagnosis has shown good results. Xukun L [19] used a state-of-the-art 3D convolutional neural network (CNN) model to collect 501 CT image datasets from 223 patients with active pulmonary TB and to collect 501 datasets as negative samples from healthy people. The detection recall rate and accuracy of this algorithm obtained values of 85.9% and 89.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the use of deep learning models in pulmonary TB diagnosis has shown good results. Xukun L [19] used a state-of-the-art 3D convolutional neural network (CNN) model to collect 501 CT image datasets from 223 patients with active pulmonary TB and to collect 501 datasets as negative samples from healthy people. The detection recall rate and accuracy of this algorithm obtained values of 85.9% and 89.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a CNN based on the CenterNet detection framework managed to automatically identify suspected regions that were strongly indicative of TB with a mAP of 0.68. More recently, Li and colleagues [ 33 ] reported a state-of-the-art three-dimensional DL model to annotate the spatial location of lesions and classify five critical CT imaging types of TB disease (miliary, infiltrative, caseous, tuberculoma, and cavitary), with a classification precision rate at 90.9%. The overall accuracy of the proposed model was similar (0.86–0.92 vs. 0.91) for six typical CT imaging findings.…”
Section: Discussionmentioning
confidence: 99%
“…The DL system managed to automatically discover the suspected regions that are strongly indicative of TB with a mAP of 0.68. More recently, Li and colleagues [31] reported a state-of-the-art 3D deep learning model to annotate the spatial location of lesions and classify ve critical CT imaging types of TB disease (miliary, in ltrative, caseous, tuberculoma, and cavitary), with classi cation precision rate at 90.9%. Our model has shown similar overall accuracy (0.86-0.92 vs. 0.91) for six typical CT imaging ndings.…”
Section: Discussionmentioning
confidence: 99%